2007
DOI: 10.1080/13506280600859706
|View full text |Cite
|
Sign up to set email alerts
|

How is spatial context learning integrated over signal versus noise? A primacy effect in contextual cueing

Abstract: Over repeated exposure to particular visual search displays, subjects are able to implicitly extract regularities that then make search more efficient-a phenomenon known as contextual cueing. Here we explore how the learning involved in contextual cueing is formed, maintained, and updated over experience. During an initial training phase, a group of signal first subjects searched through a series of predictive displays (where distractor locations were perfectly correlated with the target location), followed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
72
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(87 citation statements)
references
References 19 publications
11
72
4
Order By: Relevance
“…Although a similar interpretation had been initially proposed by Chun and Jiang (1998) to explain contextual cuing in the classic task, this latter one is currently debated. Because contextual cuing in simple stimuli arrays relies more upon the repetition of the local context than upon the global context, an explanation in terms of guidance benefit seems to poorly account for contextual cuing effects observed with the classic task (Kunar et al, 2007;however, Fiske & Sanocki, 2010;Jungé, Scholl, & Chun, 2007). Such effects might, in some part, result from enhanced feature contrast signals at the overall-salience computation Figure 6.…”
Section: Discussionmentioning
confidence: 99%
“…Although a similar interpretation had been initially proposed by Chun and Jiang (1998) to explain contextual cuing in the classic task, this latter one is currently debated. Because contextual cuing in simple stimuli arrays relies more upon the repetition of the local context than upon the global context, an explanation in terms of guidance benefit seems to poorly account for contextual cuing effects observed with the classic task (Kunar et al, 2007;however, Fiske & Sanocki, 2010;Jungé, Scholl, & Chun, 2007). Such effects might, in some part, result from enhanced feature contrast signals at the overall-salience computation Figure 6.…”
Section: Discussionmentioning
confidence: 99%
“…One barrier to processing the newly introduced regularities is that participants may become habituated to the noise in the random stream in the first half of exposure and block learning of new regularities in these stimuli later (Jungé et al, 2007;Gebhart et al, 2009). Such habituation is driven by two factors: the initial exposure to the randomness of the stimuli in the random stream, or the fact that the same stimuli were presented throughout exposure.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have suggested that the learning of regularities is subject to a primacy effect (Gebhart, Aslin, & Newport, 2009;Jungé, Scholl, & Chun, 2007;Jiang, Swallow, Rosenbaum, & Herzig, 2013;Lew-Williams & Saffran, 2012). For example, in one study (Gebhart et al, 2009) participants were first exposed to one artificial language containing syllables that reliably co-occurred in a specific order.…”
Section: Introductionmentioning
confidence: 99%
“…These spatial features in cyberspace are not consistent with actual tourist routes, and the density map shows the cores gathering at the two main entrances (Cableways A and B), highlighting the significant primacy effect of the first impression region [6,35]. From the map of the internal trail network (Figure 6), the two cableways are generally accessible; however, from the complete flow of tourist routes, they are the most accessible and controlling axes.…”
Section: Discussionmentioning
confidence: 99%